Strategic silence and concrete corrective actions in employer brand image recovery : Brands amid workplace well-being controversies - Ollanketo, Mimmi (My University, 2026)
Organizational crises may damage not only corporate reputation but also the image of the organization as an employer. This is particularly relevant in international business contexts, where organizations compete for talent across multiple borders and are evaluated by multiple stakeholders under different institutional expectations. In workplace well-being related controversies, such as concerns regarding employee treatment and working conditions, employer image recovery may depend not only on communication but also on tangible organizational change. The main research question of this thesis aims to examine how strategic silence and internal organizational change can positively contribute to employer image recovery after a crisis. Strategic silence is understood as temporary and deliberate reduction of public communication, while corrective actions refer to implemented organizational changes addressing the causes of the crisis. The thesis is conducted as a conceptual literaturebased study, examining previous research on employer branding, crisis communication strategies and legitimacy management. The theoretical foundation is supported by illustrative case examples, where the framework is applied into real-life situations. The findings suggest that communication alone may be insufficient in restoring employer image after workplace-related crises. Instead, implemented corrective actions appear central in rebuilding credibility and legitimacy. Strategic silence may function as a supportive response strategy by signalling work-in-progress and therefore allowing additional time for examining the situation and implementing changes. Overall, the thesis concludes low-communication and action-centred image repair strategies as viable alternatives to traditional models. As internal practices and working conditions have gained importance through growing digital transparency, heightened stakeholder expectations and intensified global talent competition, maintaining legitimacy across borders has become increasingly crucial for internationally operating organizations. The thesis therefore contributes to international business research by linking employer branding, crisis recovery and legitimacy management in institutionally complex environments, providing a fresh angle on the topic.

Organisatoriset kriisit voivat vahingoittaa paitsi yrityksen kaupallista mainetta, myös sen kuvaa työnantajana. Tämä on erityisen merkityksellistä kansainvälisen liiketoiminnan kontekstissa, jossa organisaatiot kilpailevat osaajista yli maarajojen ja kohtaavat useita institutionaalisia odotuksia sidosryhmien arvioinnin alaisena. Työhyvinvointikohuissa, kuten työntekijäkohtelua ja työoloja koskevissa tapauksissa, työnantajamielikuvan palautuminen voi olla riippuvaista paitsi viestinnästä, myös konkreettisista sisäisistä muutoksista. Tämän tutkielman päätutkimuskysymys tarkastelee, miten strateginen hiljaisuus ja sisäiset organisaatiomuutokset voivat edistää työnantajamielikuvan palautumista kriisin jälkeen. Strategisella hiljaisudella tarkoitetaan julkisen viestinnän väliaikaista, tietoista vähentämistä, kun taas konkreettiset korjaustoimet viittaavat toteutettuihin organisaatiomuutoksiin kriisin taustalla oleviin ongelmiin puuttumiseksi. Tutkielma on toteutettu käsitteellisenä kirjallisuuspohjaisena tutkimuksena, jossa tarkastellaan aiempaa kirjallisuutta työnantajabrändäyksestä, kriisiviestintästrategioista ja legitimiteetin hallinnasta. Teoreettinen pohja täydentyy havainnollistavilla tapausesimerkeillä, joissa esiteltyä viitekehystä sovelletaan käytännön tilanteisiin. Tulokset osoittavat, että pelkkä viestintä ei välttämättä riitä työnantajamielikuvan palauttamiseen työhyvinvointiin liittyvien kriisien jälkeen. Konkreettiset korjaustoimenpiteet sen sijaan osoittautuvat keskeisiksi uskottavuuden ja legitimiteetin uudelleenrakentamisessa. Strateginen hiljaisuus puolestaan voi toimia tukevana vastausstrategiana viestimällä sanattomasti meneillään olevasta korjausprosessista ja mahdollistamalla lisäaikaa tilanteen arviointiin ja muutosten toteuttamiseen. Kokonaisuudessaan tutkielma esittää toimintakeskeisten ja matalan viestinnän strategioiden toimivan varteenotettavina vaihtoehtoina perinteisille kriisiviestintämalleille. Koska sisäisten käytäntöjen ja työolojen merkityksellisyys ovat kasvaneet digitaalisen läpinäkyvyyden sekä sidosryhmien korkeampien odotusten myötä ja kansainvälinen kilpailu osaavista työntekijöistä kiristyy, legitimiteetin ylläpitäminen laajoilla toimintakentillä on yhä kriittisempää kansainvälisesti toimiville organisaatioille. Tutkielma osallistuu näin ollen kansainvälisen liiketoiminnan tutkimukseen yhdistämällä työnantajabrändäyksen, kriisiviestinnän ja legitimiteetinhallinnan institutionaalisesti monimutkaisissa toimintaympäristöissä ja tarjoaa aiheeseen tuoreen näkökulman.
Keywords: employer branding; employer image; institutional theory; legitimacy repair; crisis communication; strategic silence; workplace well-being; työnantajabrändäys; työnantajamielikuva; institutionaalinen teoria; legitimiteetin korjaus; kriisiviestintä; strateginen hiljaisuus; työhyvinvointi